Peranan Strategi Guru dalam Mengembangkan Karakter Islami Anak di Sekolah - Anwar, Syaiful (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2016)
Moral degradation that is now going on in Indonesian, assumed was sourced from ethical and moral crisis in religion. Akhlak and moral crisis is an indication of poor mentality of the nation and the decline of the national dignity. It can be one of sign to the destruction of the nation. Responding to these conditions, lately, character education has become one of the hot issues in education. Program of "character building" has become a priority in the era Minister of National Education (Mendiknas), Prof. Dr. Muhammad Nuh, to build the nation's character. In step of the ideals above, Islam is a religion that aims to form his people have morality and noble moral character. Therefore, character education that emphasizes ethical-religious dimension becomes relevant for application. From this, conceptually articulate character education to know how the Islamic perspective in looking at the issue of ethics and moral character in helping his people is very important to put forward. Therefore in this paper, the authors will discuss the issue comprehensively.